Synthetic Bax-Anti Bcl2 combination module actuated by super artificial hTERT promoter selectively inhibits malignant phenotypes of bladder cancer. Issue 1 (December 2016) - Liu, Li; Liu, Yuchen; Zhang, Tianbiao; Wu, Hanwei; Lin, Muqi; Wang, Chaoliang; Zhan, Yonghao; Zhou, Qing; Qiao, Baoping; Sun, Xiaojuan; Zhang, Qiaoxia; Guo, Xiaoqiang; et al.
Abstract Background The synthetic biology technology which enhances the specificity and efficacy of treatment is a novel try in biomedical therapy during recent years. A high frequency of somatic mutations was shown in the human telomerase reverse transcriptase (hTERT) promoter in bladder cancer, indicating that a mutational hTERT promoter might be a tumor-specific element for bladder cancer therapy. In our study, we aimed to construct a synthetic combination module driven by a super artificial hTERT promoter and to investigate its influence on the malignant phenotypes of bladder cancer. Methods The dual luciferase assay system was used to verify the driven efficiency and tumor-specificity of the artificial hTERT promoter and to confirm the relationship between ETS-1 and the driven efficiency of the artificial hTERT promoter. CCK-8 assay and MTT assay were used to test the effects of the Bax-Anti Bcl2 combination module driven by the artificial hTERT promoter on cell proliferation. Simultaneously, the cell apoptosis was detected by the caspase 3ELISA assay and the flow cytometry analysis after transfection. The results of CCK-8 assay and MTT assay were analyzed by ANOVA. The independent samplest -test was used to analyze other data. Results We demonstrated that the artificial hTERT promoter had a higher driven efficiency which might be regulated by transcription factor ETS-1 in bladder cancer cells, compared with wild-type hTERT promoter. Meanwhile, the artificial hTERT promoter showed a strong tumor-specific effect. The cell proliferation inhibition and apoptosis induction were observed in artificial hTERT promoter- Bax-Anti Bcl2 combination module -transfected bladder cancer 5637 and T24 cells, but not in the module -transfected normal human fibroblasts. Conclusion This module offers us a useful synthetic biology platform to inhibit the malignant phenotypes of bladder cancer in a more specific and effective way.